2023
DOI: 10.4155/fmc-2023-0207
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazole: an Emerging Privileged Scaffold in Drug Discovery

Mohammad Abrar Alam

Abstract: Pyrazole or 1 H-pyrazole, a five-membered 1,2-diazole, is found in several approved drugs and some bioactive natural products. A myriad number of derivatives of this small molecule have been reported in clinical and preclinical studies for the potential treatment of several diseases. The number of drugs containing a pyrazole nucleus has increased significantly in the last 10 years. Some of the best-selling drugs in this class are ibrutinib, ruxolitinib, axitinib, niraparib and baricitinib, and are used to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…In our quest to find antibacterial and antineoplastic agents, , we tested these novel benzothiophene compounds against several strains of Gram-positive and Gram-negative bacterial strains. To our delight, we found several compounds with potent activity against Gram-positive bacteria and A.…”
Section: Resultsmentioning
confidence: 99%
“…In our quest to find antibacterial and antineoplastic agents, , we tested these novel benzothiophene compounds against several strains of Gram-positive and Gram-negative bacterial strains. To our delight, we found several compounds with potent activity against Gram-positive bacteria and A.…”
Section: Resultsmentioning
confidence: 99%
“…Almost all Schiff bases possess promising ADMT properties (well absorbed, possess good skin permeability, and well metabolized in the liver), which may be due to the presence of the pyrazole moiety in their structures. The pyrazole motif has promising biological applications [18][19][20][21] and is effective in various disease treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we re-synthesized three sets of pyrazole-based Schiff bases (5a-f, 6a-f, and 7a-f) via the reaction of 1a-f with 2, 3, and 4, respectively, according to the literature procedures mentioned in our previous works [35,36] (Scheme 1). The pyrazole scaffold has received considerable attention because of its promising biological applications [18][19][20][21]. For examples, Mortada et al (2024) synthesized a pyrazoletriazole derivative, E, that displayed powerful inhibition of α-glucosidase and α-amylase enzymes.…”
Section: Chemistrymentioning
confidence: 99%
“…The pyrazole scaffold represents a privileged substructure in medicinal chemistry research and a number of pyrazole derivatives have been evaluated as effective compounds in different therapeutic areas [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], including infectious diseases [ 17 , 18 ] and also against MRSA [ 19 ]. In previous studies, pyrazole derivatives I ( Figure 1 ) showed significative antibacterial activity against Gram-positive antibiotic-resistant strains [ 20 ].…”
Section: Introductionmentioning
confidence: 99%